Core self-evaluation:an empirical study in the in the Colombian context - Orlando E. Contreras-Pacheco; Martha Liliana Torres-Barreto; Juan Camilo Lésmez-Peralta (Retos: Revista de Ciencias de la Administración y Economía)
core self-evaluation (CSE) refers to the essential judgments individuals make regarding their self-performance. This study aims to empi- rically examine the correlation between employee’s CSE and key organizational variables, encompassing happiness, motivation, job satisfaction, work commitment, and person-job fit. Through a cross-sectional self-administered instrument, the research delves into the perspectives of 241 employees within four retail industry companies in northeastern Colombia. Employing a partial least squares-structural equation model, the analysis explores the relationships among these variables. The results identify a lack of full reciprocity in the examined associations. When treating CSE as the dependent variable, the study validates only the hypotheses proposing job satisfaction and motivation as independent variables. Nevertheless, a significant association emerges between CSE, and all examined organizational variables when applying a supplemental analysis with inverted hypotheses. These findings emphasize the importance of adopting a multifaceted approach to enhance organizational outcomes for employees in a business setting. Furthermore, they suggest that, beyond conventional knowledge, CSR could function as a significant catalyst for various organizational behaviors, thereby advocating for its exploration and application in similar studies.